Internet connectivity disruption in India (India) - Voidly (2026)
CRITICAL severity disruption detected in India. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: IN-2026-0166
Keywords: internet disruption; IN; disruption; critical